Application of ATMFL AT89S52 microcontroller for real time temperature control system / Azarudin Yusof Mansor - Mansor, Azarudin Yusof (2007)
This project is about the application of microcontroller for real time temperature control system. The designing of the circuit included the sensor, controller, actuator and the process. In this project, the controller that has been used is a low cost ATMEL AT89S52 microcontroller. The microcontroller will control a DC fan to low, medium or high speed with depends on the different temperature from sensor. The output speed will be indicating with seven-segment display to show the low, medium, and high speed mode.